Car Dealers’ Perception Towards Digital Signage and Its’ Descriptors: An Evidence from National Car Showroom - Nur Hazwani Zolkifly; Hazliza Haron; Md Nasarudin Hussin (International Journal of Supply Chain Management, 2018)
Due to tough economic conditions, Malaysian car markets were experiencing a slowdown. Car makers, including national cars were facing huge sales fluctuations. This pressure car dealer to use various marketing methods, including digital signage to obtain sales. However, digital signage has been underutilized by car dealer despite of its potential to generate sales in other retail formats. Therefore, this paper aims to determine the perception of digital signage in car showrooms through car dealers perspectives. By means of semi-structured interviews which were conducted between June 2017 and August 2017, car dealers from North, Central and South Malaysia were interviewed to gain insight of their perceptions toward digital signage in their showrooms. The findings revealed that car dealers have mixed perceptions towards the functions of digital signage to automotive retails. However, digital signage has the potential to positively contribute to automotive sales with given conditions that four identified descriptors met suggested criteria. These findings shall be found useful to car dealers and digital signage suppliers in learning the issues, descriptors and potential of digital signage implementation in car showrooms. As a result, the research outcomes can be used in a wider context of improvements in determining whether digital signage contributes to sales by examining each descriptor from customers perspectives.